Analisis Kesalahan Ejaan dalam Teks Deskripsi Siswa Kelas VII SMP Negeri 14 Surakarta (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Language errors are the symptoms that cannot be separated from language learning. Language errors are often found in the description text of students' works. This research aims to describe the errors in writing Indonesian language spelling in a collection of descriptive text works by grade VII students of SMP Negeri 14 Surakarta. This research is a descriptive research which uses a qualitative approach. The data sources for this research are 12 descriptive texts by grade VII students of SMP Negeri 14 Surakarta. The data in this research are spelling errors in 12 student description texts. Data collection uses documentation techniques. This research is carried out with the steps of (1) collecting sample data sources; (2) analyzing data and finding spelling errors in data sources; (3) classifying errors; (4) describing spelling errors in the data; (5) evaluating errors and finding corrections. The results show that there are 108 spelling errors in the descriptive text of the students' works at SMP Negeri 14 Surakarta. These spelling errors include errors in writing capital letters, writing prepositions, writing abbreviations, writing punctuation, writing repeated words, and writing affixes.